Analysis of Production Scheduling In “Abadi” Malang Rackets And Sport Equipment Company - Erika Fera Septiana; Nurul Asfiah; Kenny Roz (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2021)
Racket and Sports Equipment Company "Abadi" Malang is engaged in manufacturing. As a result of the covid-19, the company only produces midangan. The purpose of this research is to find out and find the optimal scheduling method so that it can overcome the problem of delays in order completion. The method used is the priority rule consisting of first come first serve (FCFS), shortest processing time (SPT), longest processing time (LPT), and earliest due date (EDD). The results of the study indicate that the SPT method is a method that has the most optimal measure of effectiveness compared to the FCFS, LPT, and EDD methods. The SPT method produces an average value of 21 days of completion, 31.74% utility, an average number of jobs in the system 3.15 jobs, and a delay of 12.5 days.